Anticipation of racially motivated police brutality and youth mental health. (November 2022) - Webb, Lindsey; Jackson, Dylan B.; Jindal, Monique; Alang, Sirry; Mendelson, Tamar; Clary, Laura K.
Abstract: Purpose: Exposure to police brutality is a significant risk to adolescent mental health. This study extends this literature by exploring connections between anticipation of racially motivated police brutality and multiple facets of adolescent mental health. Methods: Students ages 14 to 18 ( n = 151) were recruited from a study administered in Baltimore City public schools. Between December 2020 and July 2021, participants completed a questionnaire assessing anticipatory stress regarding racially motivated police brutality and current mental health. Regression models examined associations between this anticipatory stress and mental health. Latent profile and regression analyses were used to examine whether anticipatory stress was more salient among adolescents with comorbid mental health symptoms, compared to those without comorbid symptoms. Results: Youth with anticipatory stress stemming from both personal and vicarious police brutality had more symptoms of anxiety, depression, and PTSD, as well as lower hope, compared to youth without anticipatory stress. The association between anticipatory stress and anxiety was stronger for girls than boys. Conclusions: Findings from this study highlight racialized police brutality as a common anticipated stressor among youth, particularly for girls. Findings have implications for policing interventions, including development of additional trainings for police officers and promoting positive police/youth interactions. Highlights: Racialized police brutality is a common anticipated stressor in youth in urban areas. This stress is tied to diminished mental health and well-being. This stress may be more impactful for girls than for boys.